Dispute Resolution and Self-Selection : An Empirical Examination of the Federal Public Sector, 1971-1982 - Swimmer, Gene; Winer, Stanley (Relations industrielles / Industrial Relations, 1993)
Unions in the Canadian federal public service have been able to unilaterally select whether any impasse in the upcoming negotiations would be resolved by a strike or arbitration. In this paper, the union's dispute resolution choice is modelled simultaneously with wage determination in the federal public service, using the self selection methodology.